Determinants of Infant Young Child Feeding Among Mothers of Malnourished Children in South Punjab, Pakistan: A Qualitative Study - Ahmed, Farooq; Malik, Najma Iqbal; Shahzad, Muhammad; Ahmad, Manal; Shahid, Muhammad; Feng, Xing Lin; Guo, Jing (Frontiers in Public Health, 2022)
Inadequate feeding is one of the most critical underlying determinants of child malnutrition. In this study, we explore infant young child feeding (IYCF) and deconstruct breastfeeding barriers in mothers of severely malnourished children in one of the most marginalized districts of Punjab province of Pakistan. Using purposive sampling, 20 lactating mothers are recruited for open-ended semi-structured interviews. Results reveal that barriers to immediate and exclusive breastfeeding include the introduction of pre-lacteal, butter, and cow or formula milk by mothers and grandmothers. Birthing difficulties and ritualizing prelacteal to transfer religion and culture cause the delay of early initiation of breastmilk. The colostrum is also discarded based on its weird physical look. Moreover, household circumstances, limited diet, extra workload, and mental stress associated with marital relationships are other significant barriers. Mothers perceive their breastmilk as thin, impotent, and of bad quality and often complain against breastmilk insufficiency due to general weakness. Furthermore, poor mothers reduce breastfeeding when the fertility burden is high, especially if a female baby is in their womb. Alternatively, outer milk is recommended but washing bottles with detergents often becomes frequent. In conclusion, immediacy, exclusivity, frequency, and duration of breastfeeding are circumscribed owing to multiple social, cultural, and economic causes. Therefore, a holistic approach combining cultural and structural causes might be more relevant for successful IYCF practices in marginalized communities of Pakistan.